Recent advancement in the field of anticonvulsants: A review - Pandey S.; Srivastava R.S. (My University, 2025)
This study emphasized on the recent developments in the field of anticonvulsant agents. The review illustrates various structural classes of compounds which were evaluated for anticonvulsant action according to the established procedure by the Antiepileptic Drug Development Program of the Epilepsy Branch, National Institute of Neurological Disorders and Stroke, National Institute of Health, USA. This review encompasses some new anticonvulsant agents of various chemical structures, and for most of the compounds the precise mechanism of action is still not known. These newer agents include: tryptamines and isotryptamines, sulfonamides (carbonic anhydrase inhibitors), derivatives of amino acids, isoindolinedione derivatives, lactams and amides, quinazolin-4-(3H)-one derivatives, y-hydroxybutyric acid (GHB) and its derivatives, semicarbazones and thiosemicarbazones. These new compounds of different structural classes could be handy for designing the future targets and in the determination of their precise mechanism of action. Nevertheless, few new drugs have brought significant advancement in the tolerability of anticonvulsant therapies. This study would be useful to design novel, effective anticonvulsant to combat epilepsy in its numerous forms, with more selective activity and least toxicity. © 2010 Bentham Science Publishers Ltd.